Engineering Innovations Vol. 15 - Retno Asih; Mubashir Ali Siddiqui; Levan Chkhartishvili (Trans Tech Publications Ltd, 2025)
The 15th volume of the journal Engineering Innovations includes articles focused on research results in modern high-entropy alloys, detection methods of food components in the food industry and the faults in the work spur gears based on vibration signal, applications of IOT in the system of smart home and smart grid and the Impact of artificial intelligence on management control processes. The presented edition will be useful for a wide circle of engineers and researchers.